Zastosowanie Internetu w międzynarodowych badaniach marketingowych - Sobocińska, Magdalena (The Usage of Internet in International Marketing Research, 2006)
Development of the Internet creates new possibilities for the international marketing research. The number of projects of marketing research on-line will be boosted along with growth of number of Internet users. The Internet can be used in the secondary and primary research. The Internet can be used in recruitment of respondents and for management realization of research as well. In marketing research are used different kinds of the Internet panels too.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 615-623